A fighting fetish: On transnational police and their warlike presentation of self - Sausdal, David (Theoretical criminology, 2021)
Transnational police readily use martial language in the stories they tell about their work. Their actual work, however, tells a different and less dramatic story. Why, then, do they insist on these warlike tales? Why is there a discrepancy between the self-representation of transnational policing and its reality? Using an ethnographic study, this article provides some answers. First, it includes an overview of three established explanations of the inclination of transnational police to represent their work in warlike terms. Next, an additional reading is presented. Building on Reiner’s discussion of “police fetishism”, this reading proposes that transnational policing actors have an idée fixe about their own professional inevitability. They blindly believe that policing must exist, but also that it has to be done combatively to truly work. In conclusion, the article contemplates what the existence of such a “fighting fetish” means in both theoretical and reform terms.